Benchmarking the Corona crisis management in two European academic libraries - Saarti, Jarmo; Balagué, Nuria (Qualitative and Quantitative Methods in Libraries; Vol 10 No 3 (2021): September issue 2021, 2021)
Since March 2020, the Corona virus has transformed the way that academic libraries have carried out their functions. The European situation deteriorated especially throughout the Mediterranean region. In contrast, in the initial wave of the virus in spring 2020, some Nordic countries like Finland, seemed to manage the situation in a more structured manner. The second wave, during the fall and winter 2020, was managed with the knowledge gathered during the first wave. We will be describing both the Corona situation and actions at the national levels in Finland and Spain as well as between the Universitat Autònoma de Barcelona Library (Spain) and the University of Eastern Finland Library (Finland). The aims of our paper and presentation will be: 1. to give an overview of the Corona situation and policy measures at the national level in both countries and 2. to identify the best practices in both academic libraries. The results also reveal how the crisis management protocols initiated in these institutions coped with the pandemic. Finally, recommendations are made with respect to the further development for crisis management in academic libraries in a rapidly changing operational environment.